Properties of zinc oxide/graphene oxide nanostructured for uv sensor application / Noor Fatin Sofea Zulkifli - Zulkifli, Noor Fatin Sofea (Faculty of Applied Sciences, 2018)
The effect of graphene oxide (GO) on the structural and optical properties of zinc oxide (ZnO) nanorods have been investigated for UV sensor applications) GO at different weight (0.05, 0.10 and 0.15g) have been mixed with ZnO solution and deposited using aqueous solution immersion method. All the samples have been characterized using X-ray Diffraction. (XRD), Field Emission Scanning Electron Microscope (FESEM) and UV-visible (UV-vis) spectroscopy. Based on the XRD pattern, all the samples show the highest peak intensities along c-axis orientation of (0 0 2) plane. The GO: ZnO films prepared at 0.05g of GO weight percentage has the highest peak intensities along c-axis orientation of (0 0 2) plane. The diameter size of ZnO and GO: ZnO nanorods at 0.05,0.10 and 0.15g weight percentage were 211,64, 50 and 60 nm, respectively. The UV-vis results show that the GO: Zno which prepared at 0.05g have the highest absorbance in UV range. Therefore, by adding GO into ZnO will influence the structural and optical properties of pure ZnO which is suitable for UV sensor applications.